Risk factors for perioperative stroke, myocardial infarction, and death in patients undergoing carotid endarterectomy under local anesthesia: a systematic review and meta-analysis - Ciccozzi, Alessandra; Riccio, Diletta; Piroli, Alba; Marsili, Ida; Mariani, Roberta; Murgia, Federico; Angeletti, Chiara; Angeletti, Paolo Matteo; Tienforti, Daniele; Marinangeli, Franco; Barbonetti, Arcangelo (Frontiers in Surgery, 2026)
BackgroundPatients with vascular disease undergoing surgery face increased perioperative risks, and those scheduled for carotid endarterectomy (CEA) represent a particularly vulnerable subgroup. This study aimed to (1) estimate the prevalence and identify predictors of adverse postoperative outcomes in patients undergoing carotid endarterectomy (CEA) under local/regional anesthesia (LA), and (2) compare these outcomes with those of general anesthesia (GA) where comparative data were available.MethodsFollowing PRISMA and MOOSE guidelines, PubMed, Scopus, and Web of Science were systematically searched for English-language studies published up to January 2025. Pooled prevalence estimates were obtained using random-effects models. Meta-regression explored associations of demographic and clinical variables with postoperative outcomes. In addition, pairwise random-effects meta-analyses were performed for studies reporting separate outcomes for LA and GA. Effect sizes were expressed as odds ratios (OR) with 95% confidence intervals (CIs), and heterogeneity was quantified using the I2 statistic.ResultsOf 267 records identified, 14 studies met eligibility criteria, including 22,302 patients undergoing CEA under LA. The pooled prevalence was 1% for stroke (95% CI: 0.01–0.02) and 0.01% for both myocardial infarction and death (95% CI: 0.00–0.01). Meta-regressions showed that male sex was significantly associated with postoperative stroke (β = 0.010, p = 0.0002), whereas older age predicted myocardial infarction (β = 0.006, p = 0.03). No significant predictors of mortality were identified. In the comparative analysis, LA was associated with a 52% lower risk of myocardial infarction and a 30% lower risk of death compared with GA, while no significant difference emerged for postoperative stroke.ConclusionCEA performed under regional anesthesia is associated with low rates of adverse postoperative events, with male sex and older age emerging as relevant predictors for stroke and myocardial infarction, respectively. Comparative evidence suggests potential advantages of LA over GA in reducing myocardial infarction and mortality, while stroke risk appears similar between anesthetic modalities.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO CRD420251066377.